2011
DOI: 10.1603/en10309
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota in Nymph and Adults of the Giant Mesquite Bug (Thasus neocalifornicus) (Heteroptera: Coreidae) Is Dominated byBurkholderiaAcquiredDe NovoEvery Generation

Abstract: The coreid bug Thasus neocalifornicus Brailovsky and Barrera, commonly known as the giant mesquite bug, is a ubiquitous insect of the southwestern United States. Both nymphs and adults are often found aggregated on mesquite trees (Prosopis spp.: Fabaceae) feeding on seedpods and plant sap. We characterized the indigenous bacterial populations of nymphs and adults of this species by using molecular and phylogenetic techniques and culturing methods. Results show that this insect's bacterial gut community has a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(53 citation statements)
references
References 47 publications
1
52
0
Order By: Relevance
“…These compounds have been found in many other heteropterans (Aldrich 1988), and bioassays using model predators have confirmed that, as in other heteropterans, they confer defensive protection to nymphs, while in adults they function as alarm pheromones (Prudic et al 2008). Past work in this system using diagnostic PCR, revealed that Wolbachia infects several organs of this bug, including their scent glands (Olivier-Espejel et al 2011). Since (E)-2-hexenal and 4-oxo-(E)-2-hexenal are strong antibacterial substances (Noge et al 2012a), the presence of bacteria in these organs was intriguing.…”
Section: Introductionmentioning
confidence: 61%
See 2 more Smart Citations
“…These compounds have been found in many other heteropterans (Aldrich 1988), and bioassays using model predators have confirmed that, as in other heteropterans, they confer defensive protection to nymphs, while in adults they function as alarm pheromones (Prudic et al 2008). Past work in this system using diagnostic PCR, revealed that Wolbachia infects several organs of this bug, including their scent glands (Olivier-Espejel et al 2011). Since (E)-2-hexenal and 4-oxo-(E)-2-hexenal are strong antibacterial substances (Noge et al 2012a), the presence of bacteria in these organs was intriguing.…”
Section: Introductionmentioning
confidence: 61%
“…In situ Hybridization Nymph DGAs were dissected and fixed with Carnoy's solution (ethanol:chloroform:acetic acid = 6:3:1 (vol/vol)) for 6 d and then treated for 7 d with 6 % H 2 O 2 in 80 % ethanol following the procedure described in Olivier-Espejel et al (2011). The universal probe Eub338 targeting bacterial 16S rRNA labeled with cyanine dye (5′-/5Cy3/ GCTGCCTCCCGTAG GAGT-3′) and a Wolbachia specific probe labeled with Cy5 (5′-/ Cy5 / AACCGACCCTATCCCTTCG-3′) were used to detect the bacteria.…”
Section: Histology and Fluorescentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Burkholderia bacterial symbionts are not acquired from the eggs in Thasus neocalifornicus Brailovsky & Barrera and must be acquired de novo, presumably from the soil, by the early instars (Olivier-Espejel et al 2011 ).…”
Section: Eggs and Ovipositionmentioning
confidence: 99%
“…Nymphal descriptions and host plant associations for several species in Mexico are given by Brailovsky et al ( 1995 ) and components of the scent fl uid have been identifi ed for nymphs of one Mexican species (Noge et al 2012 ). The biology of the North American species, Thasus neocalifornicus Brailovsky & Barrera, has been thoroughly investigated, including the chemistry of the scent glands (Prudic et al 2008 ) and the gut biota (Olivier-Espejel et al 2011 ). Mozena obtusa Uhler has been extensively studied in Texas as a potential biological control agent for mesquite in Australia and South Africa (Cuda and DeLoach 1998 ).…”
Section: Nematopodini Amyot and Serville (Plate 1911 )mentioning
confidence: 99%